Performance evaluation of the new Chemiluminescence Immunoassay CL-1200i Thyroid Panel. Issue 3 (4th May 2022) - Nicolai, Eleonora; Nuccetelli, Marzia; Sarubbi, Serena; Basile, Valerio; Perrone, Marco Alfonso; Terrinoni, Alessandro; Minieri, Marilena; Pieri, Massimo; Bernardini, Sergio
ABSTRACT: Aim of this work was to verify the analytical performance of thyroid panel tests measured by chemiluminescence immunoassay (CLIA) CL-1200i and to validate its efficacy as laboratory test for thyroid disorder. Serum samples were obtained by standard centrifugation, thawed and assayed in a blinded fashion, and in a single batch. This study compares the values of thyroid panel tests measured by Mindray CL-1200i chemiluminescent system to the Abbott platforms for TSH, FT3, FT4, and Beckman Coulter for Tg, TgAb, and TPOAb on patient serum samples. A total of 180 randomly selected patients including both hospitalized and ambulatory patients from the Policlinico Tor Vergata (PTV) of the University of Rome Tor Vergata were used. In all analyses performed, the thyroid panel tests of the Mindray platform showed discriminative ability to quantitatively assess the analyte involved in thyroid disease and disorder. This study verified that Mindray CL-1200i chemiluminescent system thyroid panel tests is a valid method for obtaining a quantitative analysis of thyroid disorders. It showed high diagnostic efficiency and could represent a valid tool with a potential reduction in time and workload for the diagnosis.